Analisis permasalahan penerapan teknologi tangki septik komunal di RW 07 Tamansari, Kelurahan Lebak Siliwangi, Kota Bandung - Kurnia, Gena Gisela; Qinthara, Dhafin; Ramadhan, Muhamad Firqi; Asifah, Nur; Ramadhan, Taufik Rizki; Dirgawati, Mila (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Domestic wastewater service with a piped system by PDAM Kota Bandung currently has not reached evenly and thoroughly to remote residential areas. In 2008, PDAM collaborated with the Environmental Services Program-United States Agency for International Development (ESP-USAID) built MCK Plus (MCK equipped with a bio-digester septic tank). This research was conducted at RW 07 Tamansari, Lebak Siliwangi Village, Bandung City and was carried out in March-May 2023. The data collected was primary data from observations, questionnaires, and interviews, while secondary data from literature studies. The survey results found that 8 MCK were abandoned and had been used as storage areas (warehouses) as well as chicken coops. For the service of 35 households, the required rectangular septic tank are 3.2 m wide, 9.6 m long, 3.2m high and the volume of the septic tank is 61.5m3. From the calculation results, the biogas produced per day can be used for cooking activities for a maximum of 2 people. Septic tanks as a technology for treating wastewater have a good impact on society if used effectively. To get the maximum potential from implementing a septic tank, it requires not only community participation, but also collaborative government institutions to support this program.